MINERAL INCLUSIONS IN ZIRCON FROM DIAMOND-BEARING MARBLE IN THE KOKCHETAV MASSIF, NORTHERN KAZAKHSTAN - Katayama I.; Ohta M.; Ogasawara Y. (My University, 2002)
In order to constrain the metamorphic evolution of deeply subducted impure marble from the Kokchetav massif, we investigated mineral inclusions in zircon, which is known to protect ultrahigh-pressure (UHP) phases from late-stage overprinting. Consequently, diamond, coesite, diopside, garnet, phlogopite, calcite, dolomite, graphite and apatite were identified as inclusion in the zircons. Silica phases were absent in the matrix, indicating they were completely consumed by the following prograde reaction: Dolomite + 2 SiO2 = Diopside + 2 CO2. The relict of coesite inclusions in zircon indicates that prograde P-T trajectory crossed cut the quartz-coesite transition before the decarbonate reaction. Matrix diopsides contain abundant exsolved phengite lamellae, whereas the exsolution is absent in the inclusions in zircon. The diopside inclusions contain higher amounts of K2O (UP to 0.56 wt%) and CaEskola component (up to 3.5 mol%) than those of the matrix (0.14 wt% and 2.1 mol%, respectively). Thus, phengite exsolution occurs in matrix pyroxene with low K2O and CaEskola components compared to inclusions in zircon. This observation indicates that decreasing K2O and CaEskola components during decompression resulted in the phengite exsolution in diopside. A trace of hydroxyl in phengite needles was perhaps initially incorporated within the precursor clinopyroxene under high-pressure conditions. The peak metamorphic P-T conditions of the impure marble are estimated to 60-80 kbar and 960-1050degreesC, derived from K2O solubility in diopside buffered by phlogopite and from the garnet-clinopyroxene geothermometer.